Subwavelength grating Fourier‐transform interferometer array in silicon‐on‐insulator. Issue 6 (22nd August 2013) - Bock, Przemek J.; Cheben, Pavel; Velasco, Aitor V.; Schmid, Jens H.; Delâge, André; Florjańczyk, Mirosław; Lapointe, Jean; Xu, Dan‐Xia; Vachon, Martin; Janz, Siegfried; Calvo, María L.
<x xml:space="preserve">Abstract</x> A planar waveguide Fourier‐transform spectrometer with densely arrayed Mach‐Zehnder interferometers is demonstrated. Subwavelength gratings are used to produce an optical path difference without waveguide bends. The fabricated device comprises of an array of 32 Mach‐Zehnder interferometers, which produce a spatial interferogram without any moving parts, yielding a spectral resolution of 50 pm and a free‐spectral range of 0.78 nm. As a result of similar propagation losses in subwavelength grating waveguides and conventional strip waveguides, loss imbalance is minimized and high interferometic extinction ratio of −25 to −30 dB is obtained. Furthermore, phase and amplitude errors arising from normal fabrication variation are compensated by the spectral retrieval process using calibration measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>